Awards and executives' financial performance preference: Evidence from China A-share listed companies. Issue 3 (3rd February 2020) - Deng, Bofu; Liu, Jia Wei; Ji, Li
Abstract : Purpose: The purpose of this paper discusses the fundamental nature of the corporate awards disclosed in the annual reports of Chinese A-share listed companies. The authors hypothesise and investigate the role of awards playing as non-financial performance, which is a Chinese characteristic, and therefore, can substitute for financial performance from the perspective of an executive's preference of financial performance. Design/methodology/approach: This study focusses on the corporate awards disclosed in company annual reports. It regards award-winning at the enterprise level as a kind of non-financial performance of Chinese enterprises, which represents achievements in the status competition and establishes good conditions for enterprises. The authors design empirical models and use data of A-share listed company to investigate the research questions and check the robustness of conclusions by eliminating endogenous problems and sample selection problems. Findings: The empirical evidence reveals that corporate awards reduce management financial performance preference. This is reflected not only in reduced current period positive accruals earnings management, which can directly improve current period financial performance but also in reduced current period negative earnings management, which can indirectly improve future financial performance. The authors also find that there is an industry spillover effect of corporate awards, which is that awards increase the financial performance preference of other company executives within the industry. Research limitations/implications: As a form of non-financial performance, corporate awards provide more reference information for investors. Currently, academic attention to this issue in China is still lacking. What is the essence of corporate awards, what economic consequences are there for listed companies and what effect is there on China's capital market development? These questions are worthy of further study. Originality/value: First, the literature on corporate awards has focussed on the effect of awards on individual behaviour, mainly considering awards as non-monetary rewards and exploring their economic consequences. Therefore, the hypothesis that awards are "Chinese-style performance" is an extension of the literature and theory related to the economic consequences of awards from the individual to the enterprise level, which is an important addition to the literature on corporate awards and their economic consequences. Second, the authors propose and prove that awards are an important demonstration of a company's competitive performance. This study provides a better understanding of how Chinese companies display their performance and the behavioural logic behind the performance demands of company management.